Expenditures of the Ministry of Defence of Ukraine: Analysis from the Perspective of Transformational Economic Prospects - Zozulinska, Maria; Artiushenko, Oleksandr (Social Development and Security, 2025)
Purpose: To investigate the relationship between military expenditures and economic growth within the context of Ukraine’s prewar and wartime economy, using rigorous econometric tools. Design/Method/Approach: This paper applies a quantitative econometric approach using historical time series data (1993–2023) on economic growth and military expenditures. The methodology combines stationarity testing (ADF), Granger causality, VAR modeling, Ridge regression, and OLS, supported by data transformation techniques, including differentiation and logarithmic scaling. Python-based statistical libraries were used to structure, test, and interpret trends and relationships. This approach ensures model stability, tests causality, and assesses budget predictability in wartime conditions. Findings: The results of the study indicate that economic growth and military expenditures in Ukraine do not have a significant statistical or causal relationship. Granger causality tests, VAR modeling, and regression analysis yielded weak or insignificant coefficients, indicating minimal interaction. Despite the war, military expenditures are not a cause of GDP growth according to Granger, and vice versa. Econometric models showed instability and low predictive power, confirming that the military budget functions independently of short-term economic indicators. Theoretical implications (if applicable): The study questions traditional assumptions that military expenditure stimulates economic growth, especially in wartime. It supports the idea that defense expenditures during wartime can function independently of macroeconomic cycles, suggesting a need to revise models that directly link public sector spending to economic growth. The author also rethink the ideology of Ukraine’s war economy in the context of emergency fiscal measures and nonlinear interactions between national security and national productivity. Originality/Value: This study contains an econometric analysis of Ukraine’s defense budget under martial law, combining VAR modeling, stationarity testing, and Ridge regression. Its novelty lies in the application of advanced time series analysis methods to real data from pre-war and wartime periods, revealing the absence of statistical significance and predictive links between economic growth and military expenditures. These findings are of strategic importance for policy makers, offering a data-driven perspective on budget sustainability, fiscal planning, and institutional reform in post-conflict economies. Research limitations/Future research: The prospect for further research involves expanding the range of time series and comparing the results with other countries. It is also advisable to apply forecasting based on machine learning methods. Paper type: theoretical-empirical.